2017
DOI: 10.1177/0734242x17697816
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for valuables from landfills and assessing their market opportunities A case study with Kudjape landfill in Estonia

Abstract: Landfill mining is an alternative technology that merges the ideas of material recycling and sustainable waste management. This paper reports a case study to estimate the value of landfilled materials and their respective market opportunities, based on a full-scale landfill mining project in Estonia. During the project, a dump site (Kudjape, Estonia) was excavated with the main objectives of extracting soil-like final cover material with the function of methane degradation. In total, about 57,777 m of waste wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 34 publications
5
27
0
1
Order By: Relevance
“…Tukey's multiple comparisons test showed that the differences among the three size categories were significant statistically. The results were in agreement with other studies that quantified CF as 46 ± 11% [28], MF as ranging between 21.8% and 31.4% [29] and FF (<24 mm) averaging 55% [30]. However, the results may differ from a number of other studies owing to different factors such as sampling procedure, selected particle size categorisation, waste type and waste age [19].…”
Section: Particle Size Distributionsupporting
confidence: 89%
“…Tukey's multiple comparisons test showed that the differences among the three size categories were significant statistically. The results were in agreement with other studies that quantified CF as 46 ± 11% [28], MF as ranging between 21.8% and 31.4% [29] and FF (<24 mm) averaging 55% [30]. However, the results may differ from a number of other studies owing to different factors such as sampling procedure, selected particle size categorisation, waste type and waste age [19].…”
Section: Particle Size Distributionsupporting
confidence: 89%
“…However, the amount of fines (<10 mm) found in Halbenrain, 49%, is comparable to those found in Kuopio, Finland, with 50-54% (Kaartinen et al, 2013); Lower Austria, Austria, with 47% (Wolfsberger et al, 2015); and Remo, Belgium, with 44±12% (Quaghebeur et al, 2013). Regarding the amount of plastics (2D and 3D plastics), Halbenrain accounts for 16.5%, whereas the amount in Kuopio, Kudjape, Lower Austria and Remo are 23%, 22.4% (Bhatnagar et al, 2017), 18%, and 17±10%, respectively.…”
Section: Composition Of the Materials Flowssupporting
confidence: 50%
“…However, under landfill conditions it is obvious that metals like Ca, Mg, K and Na, but also a significant proportion of Fe are present in oxidized form as minerals. Among these, Ca and Fe were the metals with higher concentration ranges, with 70,000-80,000 mg/kg and 30,000-50,000 mg/kg, respectively, in the fraction < 10 mm; followed by Mg, K, Na and Zn (concentrations between 500-20,000 mg/kg), Mn, Cu and Pb (concentrations around 150-400 mg/kg) and Cr, Ni, Co and Cd (concentrations below 150 mg/kg), according to Bhatnagar et al, 2017. A similar trend in terms of metal concentrations was found between all excavated pits .…”
Section: Metals Contentmentioning
confidence: 96%
“…Moreover, together the fractions < 0.425 mm and 0.425-6.3 mm constituted about 60 Particle size wt.% of the excavated landfill MSW (3-8 years old) by Jain et al, 2005; where 44.6 wt.% corresponded to the fraction < 0.425 mm and 14.5 wt.% to the fraction 0.425-6.3 mm. Excavated landfill MSW (10 years old waste), which consisted of around 54 wt.% material < 40 mm and about 46 wt.% material > 40 mm, exhibited a slight increase in the amount of the material < 40 mm with depth (Burlakovs, Kaczala et al, 2016;Bhatnagar et al, 2017). The results obtained by Kaartinen et al, 2013 indicated transport of the fraction < 20 mm (5-10 years old excavated MSW) towards the bottom layer of the landfill as well.…”
Section: Particle Size Distributionmentioning
confidence: 97%